Divergent response of aridity index to historical land use and land cover change - Tao Tang; Jun Ge; Haiyun Shi; Junji Cao (npj Climate and Atmospheric Science)
Abstract By using model simulations, we show that historical land use and land cover change since 1850 has impacted aridity index (AI) worldwide, causing divergent responses in different regions. Locally, AI tends to increase (getting humid) in reforestation regions and most humid regions. Owing to these changes, the area of the humid zone expanded insignificantly by 0.22% of the global land area at the expense of drylands.